Anthropometric profile, eating habits and physical activity levels of students in a city in the state of São Paulo - Prado,Maria Tereza Artero (2016)
OBJECTIVE: To verify the prevalence of overweight in students aged 7 to 13 years in public schools in a city in the state of São Paulo; to compare the eating habits and physical activity levels of the students with those of their parents; to relate eating habits and physical activity levels to gender. METHODS: This was a transverse observational study. Eighty-two children of both genders, aged 7 - 13 years, were evaluated, anthropometric data collected and body mass index for age was classified as per the Brazilian Ministry of Health "Food and Nutrition Monitoring System" (SISVAN); concurrently we applied a questionnaire for the analysis of physical activity levels and eating profiles for students and their parents. Data were analyzed through Kolmogorov-Smirnov tests, unpaired Student t test or Mann Whitney; for correlation analysis, we employed the Spearman or Pearson tests. RESULTS: In this study, half of the students were found to be overweight, with an increased abdominal circumference. We also observed that better eating habits correlated with greater physical activity. Students consumed more fried food, sweets and fruit and ate more often than their parents; few of these parents regularly perform physical activity. CONCLUSIONS: Excess weight has been found in half of the students evaluated in a small town with a high Human Development Index. It was also found that boys presented higher level of physical activity, number of meals and lower sweet intake. Furthermore, it was observed that better eating habits were associated with the level of physical activity.